Falls From Height: Injury and Mortality. Issue 2 (1st June 2012) - Dickinson, A; Roberts, M; Kumar, A; Weaver, A; Lockey, DJ
Abstract : Objectives: To determine how Injury Severity Score (ISS) and mortality relate to height fallen, and to determine other predictors of mortality including intent and body region injured. Methods: A pre-hospital retrospective, observational database study was conducted. Injured or deceased patients following a fall from height (FFH), aged 16 or over, attended to by London Helicopter Emergency Medical Services (HEMS), between Jan 2008 to July 2009 were included in the study. In addition to the database, HEMS mission 'run sheets' provided further information. Results: 117 (91 males and 26 females) patients met the inclusion criteria. The mean age was 37 years (range 16 - 85). 34/117 (29%) died. The mean ISS was 28.6 (median 17) and the mean height fallen 9.9m (3 rd floor). In the group that died the mean height was 16.7m (5 th floor). Height fallen was found to be a significant predictor of mortality (p<0.001), as were injuries to the chest and/or head (p<0.05). In patients with head and chest injuries, a 50% mortality rate was estimated to occur at falls from 10.5m, compared to 22.4m in those without injuries to head or chest. Deliberate falls were more common amongst females than males (chi-squared test, p=0.001), were associated with greater ISS (Mann Whitney test, p<0.001) and were more likely to result in death (chi-squared test, p<0.001). Conclusions: Height fallen correlates with ISS and is a significant predictor of death. Chest and/or head injuries significantly increased the likelihood of death following a FFH. This information may enhance triage criteria applied to tasking of emergency response vehicles, and strategies in injury prevention. Other potential predictors of mortality were not found to be significant.